Cellular responses in the FGF10‐mediated improvement of hindlimb regenerative capacity in Xenopus laevis revealed by single‐cell transcriptomics. (20th June 2022) - Yanagi, Nodoka; Kato, Sumika; Fukazawa, Taro; Kubo, Takeo
Abstract: Xenopus laevis tadpoles possess regenerative capacity in their hindlimb buds at early developmental stages (stages ~52–54); they can regenerate complete hindlimbs with digits after limb bud amputation. However, they gradually lose their regenerative capacity as metamorphosis proceeds. Tadpoles in late developmental stages regenerate fewer digits (stage ~56), or only form cartilaginous spike without digits or joints (stage ~58 or later) after amputation. Previous studies have shown that administration of fibroblast growth factor 10 (FGF10) in late‐stage (stage 56) tadpole hindlimb buds after amputation can improve their regenerative capacity, which means that the cells responding to FGF10 signaling play an important role in limb bud regeneration. In this study, we performed single‐cell RNA sequencing (scRNA‐seq) of hindlimb buds that were amputated and administered FGF10 by implanting FGF10‐soaked beads at a late stage (stage 56), and explored cell clusters exhibiting a differential gene expression pattern compared with that in controls treated with phosphate‐buffered saline. The scRNA‐seq data showed expansion of fgf8‐ expressing cells in the cluster of the apical epidermal cap of FGF10‐treated hindlimb buds, which was reported previously, indicating that the administration of FGF10 was successful. On analysis, in addition to the epidermal cluster, a subset of myeloid cells and a newly identified cluster of steap4 ‐expressing cells showed remarkable differences in their gene expression profiles between the FGF10‐ or phosphate‐buffered saline‐treatment conditions, suggesting a possible role of these clusters in improving the regenerative capacity of hindlimbs via FGF10 administration.